2021
DOI: 10.3390/nu13103499
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effects of Spirulina platensis, Golden Kiwifruit Flesh, and Golden Kiwifruit Peel Extracts Individually or in Combination against Indomethacin-Induced Gastric Ulcer in Rats

Abstract: This study was conducted to investigate the therapeutic effect of hydro-alcoholic extract of Spirulina platensis (SP), golden kiwifruit (Actinidia chinensis) flesh (KF), and golden kiwifruit peel (KP) individually or in combination (SFP) on indomethacin-induced gastric ulcer in rats. Negative control rats (GI) were orally administered distilled water in parallel with other treatments. The positive control rat group (GII) was administered 30 mg kg-1 indomethacin to induce gastric ulcers. The KF and KF extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…The exact mechanism through which Aloe vera decreased serum gastrin is unclear. Our present findings agree with previous studies that revealed a reduction in serum gastrin level after administration of plant extracts, which have an antiulcer effect [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…The exact mechanism through which Aloe vera decreased serum gastrin is unclear. Our present findings agree with previous studies that revealed a reduction in serum gastrin level after administration of plant extracts, which have an antiulcer effect [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Treatment with kiwi extract greatly boosted antioxidant enzyme levels, considerably reducing ROS and inhibiting lipid peroxidation in T2DM more efficiently than treatment with insulin. These results were rather similar to those of a study of Aleid et al [ 34 ], as kiwi extract upregulated SOD, CAT, GSH, and GPx levels and mitigated lipid peroxidation against indomethacin-induced oxidative stress.…”
Section: Discussionsupporting
confidence: 91%
“…The gastric mucosal barrier lacks immune cells, but it has the ability to provide adequate cell concentrations when needed through the bloodstream [5]. Neutrophil in ltration, including gastric mucosal lesions, has been reported to participate in the process of injury and in ammation by accumulating and releasing tissue-degrading chemicals in multiple tissues [22]. CD4 and CD8 T cells and plasma cells are distributed in the lamina propria of the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%